2022
DOI: 10.1002/we.2757
|View full text |Cite
|
Sign up to set email alerts
|

Validation of near‐shore wind measurements using a dual scanning light detection and ranging system

Abstract: This paper reports results from a 2-month validation campaign of near-shore wind measurements taken by a dual scanning light detection and ranging (LiDAR) system at a coastal site in Japan. A meteorological mast and a vertical profiling LiDAR device were deployed at an offshore research station approximately 1.5 km from the coast.Offshore winds at heights of 66, 120, and 180 m above sea level were observed by the scanning LiDAR system. Comparisons with a sonic anemometer found that the radial velocities had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Cheynet et al (2021) used a sLiDAR with a fixed line-of-sight (LOS) at a fixed elevation angle and discussed the vertical profile of the radial wind speed (RWS) along the LOS with the limitations that the vertical profile is measured over a large horizontal distance. Shimada et al (2020) and Shimada et al (2022) successfully validated a method to use a sLiDAR from the shore to probe the horizontal wind speed (HWS) at a single height above the water surface using a PPI scan (Plane Position Index). These experiments are promising and efforts are still needed to measure reliable vertical profiles of the HWS near the coast.…”
Section: Introductionmentioning
confidence: 99%
“…Cheynet et al (2021) used a sLiDAR with a fixed line-of-sight (LOS) at a fixed elevation angle and discussed the vertical profile of the radial wind speed (RWS) along the LOS with the limitations that the vertical profile is measured over a large horizontal distance. Shimada et al (2020) and Shimada et al (2022) successfully validated a method to use a sLiDAR from the shore to probe the horizontal wind speed (HWS) at a single height above the water surface using a PPI scan (Plane Position Index). These experiments are promising and efforts are still needed to measure reliable vertical profiles of the HWS near the coast.…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Due to their high flexibility and range, long range scanning lidars offer great potential for many applications in the wind industry. They can perform high accuracy measurements of the wind conditions in distances up to several kilometres [1][2][3][4]. In recent years they have been used extensively in experiments characterising wind conditions and flow for wind energy application and research such as wakes [5][6][7][8], complex terrain effects [9,10], blockage [11] or power curve verification [12].…”
mentioning
confidence: 99%
“…For offshore deployment, profiling LiDARs installed on the floating buoys are considered as economic alternative to the conventional met-masts (Viselli et al, 2019). Single or dual scanning LiDARs on the other hand are being deployed at coasts to perform measurement at near-shore offshore sites (Shimada et al, 2020(Shimada et al, , 2022. However, LiDARs can only measure wind speed components along the beam direction, commonly known as radial wind speed (u r ).…”
mentioning
confidence: 99%
“…Newsom et al (2015) compared the wind data retrieved from dual-Doppler LiDAR measurement against the measurement of sonic anemometer installed on the 60 m tall met-mast and reported the correlation coefficient of 0.97 for mean wind speed and difference of less than 0.1 • for wind direction. In their validation campaign of dual scanning LiDAR, Shimada et al (2022) reported that in addition to 10-min average wind speeds and directions, the system could also give turbulence intensity values comparable to…”
mentioning
confidence: 99%